Research on the Construction of Emergency Network Public Opinion Emotional Dictionary Based on Emotional Feature Extraction Algorithm - Hui, Fang (Frontiers in Psychology, 2022)
How to strengthen emergency management and improve the ability to prevent and respond to emergencies is an important part of building a harmonious socialist society. This paper analyzes and discusses the reshaping of group values by emergencies in the new media environment, analyzes the psychological motivation of emergencies based on the emotional feature extraction algorithm, and constructs a domain emotional dictionary for online public opinion analysis. The results show that the information sharing process is full of chaotic symbols and uncertain meanings, and the interaction process between the receiver and the sender in crisis communication is more complicated. Because of the great differences in different experiences and circumstances among different groups, there will be great differences in views and perspectives of the same event. A variety of views and opinions collide and merge with each other, and even intensify the evolution, thus promoting the expansion and upgrading of public opinion. Emotional analysis method can quickly and efficiently identify the emotional polarity of netizens in online public opinion events, and then fully understand the overall emotional tendency of netizens, which plays an important role in improving the public opinion supervision ability of the government and relevant departments and maintaining public safety.